Modelling spatial dispersion of contaminants from shipping lanes in the Baltic Sea. (December 2021) - Maljutenko, Ilja; Hassellöv, Ida-Maja; Eriksson, Martin; Ytreberg, Erik; Yngsell, Daniel; Johansson, Lasse; Jalkanen, Jukka-Pekka; Kõuts, Mariliis; Kasemets, Mari-Liis; Moldanova, Jana; Magnusson, Kerstin; Raudsepp, Urmas
Abstract: Major sources of pollution from shipping to marine environments are antifouling paint residues and discharges of bilge, black, grey and ballast water and scrubber discharge water. The dispersion of copper, zinc, naphthalene, pyrene, and dibromochloromethane have been studied using the Ship Traffic Emission Assessment Model, the General Estuarine Transport Model, and the Eulerian tracer transport model in the Baltic Sea in 2012. Annual loads of the contaminants ranged from 10 −2 tons for pyrene to 100 s of tons for copper. The dispersion of the contaminants is determined by the surface kinetic energy and vertical stratification at the location of the discharge. The elevated concentration of the contaminants at the surface persists for about two-days and the contaminants are dispersed over the spatial scale of 10-60 km. The Danish Sounds, the southwestern Baltic Sea and the Gulf of Finland are under the heaviest pressure of shipborne contaminants in the Baltic Sea. Graphical abstract: Unlabelled Image Highlights: Pollution load and dispersion from main waste streams of the ships is simulated. Basin scale approach for pollution load and dispersion is used. The characteristic time- and spatial scales of pollutant's dispersion are 2 days and 10-60 km. Mean circulation and vertical mixing define the marine areas under pollution pressure.